SINTESIS DAN KARAKTERISTIK PUPUK ORGANIK LIMBAH TONGKOL JAGUNG DENGAN PENAMBAHAN KOMPOSISI DEDAK DAN EM4 - Setyawati, Harimbi; Sari, Fitria Rekno (jurnal ATMOSPHERE, 2025)
This study aims to evaluate the effect of variations in the volume of EM4 bioactivator and the amount of bran on the characteristics of organic fertilizer made from corncob waste. The background of this study is the need for an alternative fertilizer that is environmentally friendly, affordable, and utilizes agricultural waste. The variations in the volume of EM4 used were 15 mL, 20 mL, and 25 mL, and the amount of bran was 5, 15, 25, 35, and 45 grams. The parameters analyzed included C/N content, nutrient content (N, P, K), water content, and pH, referring to the SNI 7763:2018 and SNI 7763:2024 standards. The results showed that the combination of EM4, bran, and fermentation time significantly affected the quality of organic fertilizer. Treatment with 35 grams of bran and 15 mL of EM4 for 30 days produced the highest nitrogen content of 0.53%, while the highest phosphorus and potassium contents of 0.64% and 0.82%, respectively, were obtained in the treatment of 25 mL of EM4 and 25 grams of bran for 30 days. The lowest C/N content of 20.51 was also achieved in this treatment, meeting the maximum SNI standard of 25. The water content of all treatments ranged from 2–3%, and the pH was in the range of 4–7, both in accordance with SNI standards. Thus, it can be concluded that increasing the amount of nutrients, bioactivator volume, and fermentation time play an important role in accelerating decomposition, increasing nutrients, and producing organic fertilizer that meets national quality standards